The Thermal Mode Crucial Influence on the ZnSeS QDs Formation - Chylii, Maksym; Loghina, Liudmila; Kadeřávková, Anastasia; Houdek, Jakub; Vlček, Miroslav (IEEE (Institute of Electrical and Electronics Engineers), 2022)
The qualitative and quantitative diversity of existing methods for the synthesis of chalcogenide nanomaterials is constantly being updated. Attempts to improve an already functioning synthesis scheme may lead to the emergence of a new promising directions. It turned out that the ability of substituted thio- and selenoureas to form stable complexes with metal carboxylates can allow one-pot and hot-injection methods to be combined in the ZnSeS quantum dots (QDs) synthesis. After the formation of zinc linoleate complexes with various substituted thio- and selenoureas in a single reaction system at relatively low temperatures (80 °C), we introduced them into a medium heated to the desired temperature. The complexes decomposing at different rates led to the formation of ZnSeS QDs of various shapes and sizes. Despite these differences, the nanocrystals grew in the same cubic phase at different nucleation and growth temperatures. It was demonstrated that even ZnSe0.1S0.9 and ZnSe0.3S0.7 QDs prepared at such low, for the growth of chalcogenide semiconductors, temperatures (160 °C and 180 °C) have a narrow size distribution and a good quantum yield (PL QY up to 24 %). In general, the optical characteristics of the synthesized nanomaterials enable further development of this synthesis method and transfer of it to other compositions.
Kritický vliv termálního modu při formování ZnSeS kvantových teček
Keywords: methodology; photoluminescence; substituted selenoureas; substituted thioureas; ZnSeS quantum dots; metodologie; fotoluminiscence; substituované selenomočoviny; substituované thiomočoviny; ZnSeS kvantové tečky